Chromosome-specific panels of tri- and tetranucleotide microsatellite markers for multiplex fluorescent detection and automated genotyping: evaluation of their utility in pathology and forensics. - Lindqvist, A K; Magnusson, P K; Balciuniene, J; Wadelius, C; Lindholm, E; Alarcón-Riquelme, M E; Gyllensten, U B (Genome Research, 1996)
A set of 391 microsatellite markers (Weber set 6), 85% of which consist of tri- and tetranucleotide repeat markers, were used to design chromosome-specific panels that allowed for a high degree of multiplexing with respect to the fragment size range and fluorophore (FAM, HEX, TET). This marker set has an average coverage of 10.5 cM, with the largest gap being 28.1 cM. The markers were divided into 49 panels, with a maximum degree of multiplexing of 15 markers per panel. The utility of the markers for analysis of DNA from blood, hair, and formalin-fixed archival tissue biopsies was evaluated with respect to amplification efficiency, product yield, and degree of preferential amplification of the shorter allele in heterozygotes. The amplification efficiency was inversely related to repeat length and amplicon length. Based on the analysis of DNA from formalin-fixed biopsies, 51 markers suitable for loss of heterozygosity (LOH) studies were identified. The utility of the marker set for genome scanning, LOH, and forensic analyses is discussed.